Hubungan Antara Kekuatan Otot Tungkai Terhadap Ketepatan Menendang Bola ke Arah Gawang pada Permainan Sepak Bola Siswa SMK N 1 Modoinding - Jeinal Korah; Anuardin Mokoagow; Maxi Moleong (STIKES Columbia Asia Medan, 2025)
The purpose of this study was to determine the relationship between leg muscle power and football shooting ability of SMK N 1 Modoinding students. This type of research is correlational research. The population in this study were 58 students. The sampling technique was cluster sampling of players aged 14-15 years totaling 20 people. The instruments used were the standing broad jump test and the football shooting test. The results of the calculations obtained a correlation index of 0.472. This value is in the range between 0.4 - 0.70 with a moderate correlation category. The r table value in a sample of 20 or DF = 18 people is 0.444. thus the r count value> r table or 0.472> 0.444. the t count value = 2.27 and the t table value is 2.10. Thus t count> t table or 2.27> 2.10. The conclusion of this study is that there is a significant relationship between leg muscle explosive power and football shooting ability of SMK N 1 Modoinding students. The calculated r value = 0.472 and the table r value = 0.444. The calculated t value = 2.27 and the table t value = 2.10.